PENGEMBANGAN POTENSI DESA WISATA SENDANGDALEM, KEBUMEN, JAWA TENGAN SEBAGAI DAYA TARIK WISATA - Eny Endah Pujiastuti; Retno Hendariningrum; Panji Dwi Ashrianto; Tegar Koraag (at-tamkin: Jurnal Pengabdian kepada Masyarakat, 2023)
Sendangdalem Tourism Village is located in Sendangdalem, Padureso District, Kebumen Regency, Central Java. Prime tour packages are river tubing, spiritual. This community service programe analyzes the potential of Sendangdalem Village. The programes are carried out by conducting in-depth interviews, observations and discussions with the village government, community groups and tourism village management groups (pokdarwis). The result of this activity is potential mapping of Sendangdalem village. This potential mapping will be the basis for the development of tour packages from the Sendangdalem tourism village. Based on the results of potential mapping, it can be seen that the attraction for tourists besides of the daily-basis life of the community, it can become a community-based tourist attraction in Kebumen Regency.